Prescription of Antihypertensive and Antianginal Medications within the Conditions of Outpatient Treatment of Patients with Ischemic Heart Disease Along with Hypertension - Tetiana Nehoda (Journal of Global Pharma Technology, 2020)
Abstract Cardiovascular morbidity leads the world in the morbidity rate structure. An arterial hypertension and a stable angina are widely occurring among the population and, in terms of medical and social significance, stand at the head of the circulatory system diseases. The combination of these diseases is observed in 2/3 of patients. An important challenge for cardiology is to ensure a rational approach to the choice of medications for effective antianginal and antihypertensive therapy, its compliance with accepted treatment quality standards, the development of clear and scientific-based criteria for the use of medications, improvement of the patients’ quality of life while reducing the economic costs for medications supply. Purpose. To develop an approach to the optimization of medications supply for patients with ischemic heart disease in combination with arterial hypertension in inpatient and outpatient practice, based on the use of pharmacoeconomic and pharmacoepidemiological researches. Materials and methods. To assess the prescription structure of the various groups of antihypertensive and antianginal medications, an analysis of the past medical history in patients with ischemic heart disease in combination with arterial hypertension was carried out. Variation statistics methods have been applied in mathematical data processing. Results. Beta-blockers prevailed, followed by angiotensin-converting enzyme inhibitors, calcium channel blockers, and diuretics were found in the structure of medicinal benefits when prescribing pharmacotherapy to patients with stable angina pectoris with arterial hypertension. Conclusions. As a result of the research, it was revealed that the combination therapy in most cases was based on beta-blockers, angiotensin-converting enzyme inhibitors, diuretics in various combinations with each other.